Review: A. Siemieniewski and M. Kiwka, Christian Charismatic Movements: Threat or Promise?, Vandenhock & Ruprecht Verlage, Göttingen 2021, ss. 353. - Marciniak, Michał (Warszawskie Studia Teologiczne, 2024)
This article is a review of the book by A. Siemieniewski and M. Kiwka titled Christian Charismatic Movements: Threat or Promise?, published in 2021 in Göttingen by the publishing house Vandenhock & Ruprecht Verlage.